A novel SYBR-based duplex qPCR for the detection of gene dosage: detection of an APC large deletion in a familial adenomatous polyposis patient with an unusual phenotype - Torrezan Giovana; da Silva Felipe Cavalcanti; Krepischi Ana Cristina; dos Santos Érika Maria; Rossi Benedito; Carraro Dirce (BMC, 2012)
Abstract Background Familial adenomatous polyposis (FAP) is a hereditary colorectal cancer syndrome caused by a loss of function of the APC gene. Large deletions in APC are a common cause of FAP; despite the existence of a variety of gene dosage detection methodologies, most are labor intensive and time and resource consuming. Methods We describe a new duplex qPCR method for gene dosage analysis based on the coamplification of a target and a reference gene in a SYBR Green reaction, followed by a comparison of the ratio between the target and the reference peaks of the melting curve for the test (patient) and control samples. The reliability of the described duplex qPCR was validated for several genes (APC, HPRT1, ATM, PTEN and BRCA1). Results Using this novel gene dosage method, we have identified an APC gene deletion in a FAP patient undergoing genetic testing. Comparative genomic hybridization based on microarrays (aCGH) was used to confirm and map the extent of the deletion, revealing a 5.2 MB rearrangement (5q21.3-q22.3) encompassing the entire APC and 19 additional genes. Conclusion The novel assay accurately detected losses and gains of one copy of the target sequences, representing a reliable and flexible alternative to other gene dosage techniques. In addition, we described a FAP patient harboring a gross deletion at 5q21.3-q22.3 with an unusual phenotype of the absence of mental impairment and dysmorphic features.